The 'Fat' Female Body - Murray, S. author. aut Link
VIII, 196 p.
Keywords: Investigating the current interest in obesity and fatness, this book explores the problems and ambiguities that form the lived experience of 'fat' women in contemporary Western society. Engaging with dominant ideas about 'fatness', and analysing the assumptions that inform anti-fat attitudes in the West, The 'Fat' Female Body explores the moral panic over the 'obesity epidemic', and the intersection of medicine and morality in pathologising 'fat' bodies. It contributes to the emerging field of fat studies by offering not only alternative understandings of subjectivity, the (re)production of public knowledge(s) of 'fatness', and politics of embodiment, but also the possibility of (re)reading 'fat' bodies to foster more productive social relations.